Synthesis of (-)-xialenon A by enantioselective alpha-deprotonation-rearrangement of a meso-epoxide - Hodgson, D; Galano, J; Christlieb, M (2003)
The first total synthesis of (-)-xialenon A was achieved via enantioselective transannular desymmetrisation of a substituted cycloctene oxide using an organolithium/(-)-α-isosparteine combination. Oxidation of the resulting bicyclo[3.3.0]octanol gave an enone which underwent stereoselective conjugate allylation; subsequent α′-hydroxylation on the more hindered face of a derived enone using hypervalent iodine chemistry led to the natural product. © 2003 Elsevier Ltd. All rights reserved.